2005
DOI: 10.1128/mcb.25.22.10171-10182.2005
|View full text |Cite
|
Sign up to set email alerts
|

Pendrin Is a Novel In Vivo Downstream Target Gene of the TTF-1/Nkx-2.1 Homeodomain Transcription Factor in Differentiated Thyroid Cells

Abstract: Thyroid transcription factor gene 1 (TTF-1) is a homeobox-containing gene involved in thyroid organogenesis. During early thyroid development, the homeobox gene Nkx-2.5 is expressed in thyroid precursor cells coincident with the appearance of TTF-1. The aim of this study was to investigate the molecular mechanisms underlying thyroid-specific gene expression. We show that the Nkx-2.5 C terminus interacts with the TTF-1 homeodomain and, moreover, that the expression of a dominant-negative Nkx-2.5 isoform (N188K)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 63 publications
2
22
1
Order By: Relevance
“…In FRTL-5 rat thyroid cells, low doses of TSH do not induce SLC26A4 mRNA determined by Northern blot analyses [37]. This contrasts with findings in the same cell line documenting induction of SLC26A4 mRNA by RT-PCR after exposure to TSH and forskolin [42], as well as findings in the PCCL3 rat thyroid cell line reporting increased expression of pendrin mRNA, determined by RT-PCR, and protein after exposure to high doses of TSH, forskolin and 8-Bromo-cAMP [43]. It is well established, that iodide efflux at the apical membrane is rapidly accelerated by TSH [44][45][46].…”
Section: Expression and Putative Function Of Pendrin In The Thyroidcontrasting
confidence: 54%
“…In FRTL-5 rat thyroid cells, low doses of TSH do not induce SLC26A4 mRNA determined by Northern blot analyses [37]. This contrasts with findings in the same cell line documenting induction of SLC26A4 mRNA by RT-PCR after exposure to TSH and forskolin [42], as well as findings in the PCCL3 rat thyroid cell line reporting increased expression of pendrin mRNA, determined by RT-PCR, and protein after exposure to high doses of TSH, forskolin and 8-Bromo-cAMP [43]. It is well established, that iodide efflux at the apical membrane is rapidly accelerated by TSH [44][45][46].…”
Section: Expression and Putative Function Of Pendrin In The Thyroidcontrasting
confidence: 54%
“…Adequate nutritional iodide intake from vegetable and dairy food products (Scinicariello et al 2005) may compensate for an iodide transport deficit, thereby maintaining the euthyroid status. In conclusion, we speculate that serum thyroglobulin level is elevated by an abnormal iodide-trapping mechanism caused by pendrin dysfunction during infancy and that thyroid function can be rescued by some genetic (Royaux et al 2000;Dentice et al 2005) or environmental cofactors, such as nutritionally supplied iodide, after the age of 10 years. Inadequate compensation may lead to goiter.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that Nis transcription is regulated by the TSH/TSHR-mediated activation of the PKA pathway (9,48). Another study indicated that PAX8 regulates Nis transcription by binding directly to the NUE promoter region, which is critical for Nis transcriptional regulation (46), while TTF1 has been reported to play a role in the regulation of Pds transcription (49). ChIP-Seq analysis revealed that GLIS3 is associated with several TH biosynthetic genes that are suppressed in the thyroid gland of Glis3KO mice, including Pds and Nis, indicating that their transcription is directly regulated by GLIS3 ( Figure 6C and Supplemental Table 3).…”
Section: 2mentioning
confidence: 99%